The real Wizard of Oz - Loncraine, Rebecca (Gotham Books, 2009)
Explores the life of the unconventional author and entrepreneur, examining the era in which he lived and its influence on his work.
Keywords: Biografie; Baum; L. Frank; Baum; L. Frank <1856-1919>; Wizard of Oz; Authors; American; Storytellers; Children's stories; American; Fantasy fiction; American